Teachers' Wellbeing/Malaise: Which Resources and Efforts at Individual, Group and Organizational Levels?. (2nd June 2015) - Gozzoli, Caterina; Frascaroli, Daniela; D'Angelo, Chiara
Abstract: The social productive environment has changed rapidly generating new opportunities and challenges for individuals, groups, and organizations. The school-world is affected by these general changes and also subject to constant specific pressure (e.g. reforms, resources reallocation, precariousness, increasinglycomplex demands).In this scenario teachers play a crucial role.The research aims at investigating which are resources and efforts perceived by teachers and how these influence their wellbeing or malaise.We explored teachers' professional histories and their perception of their work group and work context(s).A phenomenological approach was adopted;50 high-school teachers were involved; semi-structured interviews and the "Professional Life-Space Drawing" were used; content analysis and a descriptive-phenomenological analysis of Drawings were conducted. Results permit the description of different professional situations.